Turbulent Mixing Inferred from CTD Datasets in the Western Tropical Pacific Ocean - Adi Purwandana; Mochamad Riza Iskandar (Marine Science Department Diponegoro University, 2020)
The spatial pattern of energetic aspect related to vertical mixing processes of the water masses in the western tropical Pacific Ocean is characterized in this study. Turbulent kinetic energy dissipation rates and vertical eddy diffusivities in this region are estimated from archived CTD profiles from World Ocean Database (WOD). The dissipation rates are estimated using the improved Thorpe method which considered the canonical Garret-Munk background dissipation rate and the typical lowest value dissipation rate from microstructure measurements, 10-10 m2s-3. Enhanced dissipation rates of 10-8-10-7 m2s-3 were found in the region known as an active area where two Pacific water masses from different sources intersect and strong mesoscale circulations exist while lower dissipation of less than 10-8 m2s-3 was found in the less active regions. A comparison with recent 3D hydrostatic model of M2 internal tide shows less agreement dissipation rates of the model with the observations, with the decreasing trend of discrepancy towards deeper. This suggested that topography roughness, homogenous stratifications yet lacking of background circulations set in the model were not sufficient to reproduce dissipation in the region with strong background mesoscale circulations. It was indicated that the main contributor for vertical overturning events occurred in this region is due to strong shear instabilities enhanced by background circulations. A direct method estimates using vertical microstructure profiler is suggested to validate this indirect method in the future.